2016
DOI: 10.4103/2008-322x.188390
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal injection of bevacizumab in primary vitrectomy to decrease the rate of retinal redetachment: A randomized pilot study

Abstract: Purpose:To evaluate the effect of intravitreal bevacizumab (IVB) as a surgical adjunct in prevention of proliferative vitreoretinopathy (PVR) after retinal detachment surgery.Methods:In this controlled, randomized pilot study, 27 patients with primary retinal detachment undergoing pars plana deep vitrectomy were included. Of these, 12 received IVB at the end of procedure. The anatomic success and best corrected visual acuity (BCVA) were compared to the control group at months 3 and 6 postoperatively.Results:At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…There is a paucity of studies investigating the effect of intravitreal bevacizumab as a surgical adjunct for the prevention of PVR after RRD surgery [15][16][17]27]. All failed to demonstrate any clinical benefit, but they only considered eyes with advanced stages of PVR [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of studies investigating the effect of intravitreal bevacizumab as a surgical adjunct for the prevention of PVR after RRD surgery [15][16][17]27]. All failed to demonstrate any clinical benefit, but they only considered eyes with advanced stages of PVR [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of PVR after retinal reattachment surgery is a frustrating event to retinal surgeons. In the past two decades, various drugs including steroids ( 32 ), methotrexate ( 8 , 33 ), isotretinoin ( 7 ), and anti-VEGF reagents ( 9 ) have been tested in clinical trials to prevent postoperative PVR. However, none of them was routinely used in patients with RD due to the uncertainty of efficacy and possible retinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammation process, as well as the proliferation and migration of retinal pigment epithelium (RPE) cells, glial cells, and macrophages, are involved in the onset and development of PVR (6). Based on the understanding of these pathogeneses, various anti-inflammatory, and anti-metabolic drugs have been used in clinical trials to prevent the formation of postoperative PVR (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Another small study found that adjunctive intravitreal bevacizumab following PPV for eyes with RD with up to grade B PVR did not lead to improved anatomic success or improved best-corrected visual acuity at either 3 or 6 months. 19 Finally, one study explored whether serial intra-SiO bevacizumab injections given intraoperatively and at postoperative months 1, 2, and 3 had benefits for patients undergoing PVR-related surgery. 20 The study found no improvement in retinal reattachment rate or visual acuity in the bevacizumab group versus control.…”
Section: Pharmacologic Treatments For Pvrmentioning
confidence: 99%